Sequence dependent lipid-mediated effects modulate the dimerization of ErbB2 and its associative mutants - Prasanna, Xavier; Praveen, P. J.; Sengupta, Durba (Physical Chemistry Chemical Physics, 2013)
The association of transmembrane helices is an important event in several biological processes, but the factors governing association, especially the non-specific environmental effects, have still not been elucidated. Here, we use coarse-grain molecular dynamics simulations to study the association of ErbB2 transmembrane helices and three ``oncogenic mutants.'' Self-assembly simulations and the dimerization free-energy profiles confirm an energetically-favorable dimerized state for both the wildtype and the mutants. The dissociation free energy of all three mutants is calculated to be larger than the wildtype peptide. Along with favourable protein-protein interactions, non-specific environmental effects are observed to contribute to the association. In particular, local bilayer thinning along with membrane perturbations are seen around the mutants. The membrane perturbations are reduced upon helix association, suggesting that lipid chain packing is an important driving force for helix dimerization. Our results highlight the importance of both specific as well as non-specific driving forces in the association of transmembrane helices.

Structural insights and functional implications of inter-individual variability in beta(2)-adrenergic receptor - Tandale, Aditi; Joshi, Manali; Sengupta, Durba (Scientific Reports, 2016)
The human beta(2)-adrenergic receptor (beta(2)AR) belongs to the G protein-coupled receptor (GPCR) family and due to its central role in bronchodilation, is an important drug target. The inter-individual variability in beta(2)AR has been implicated in disease susceptibility and differential drug response. In this work, we identified nine potentially deleterious non-synonymous single nucleotide polymorphisms (nsSNPs) using a consensus approach. The deleterious nsSNPs were found to cluster near the ligand binding site and towards the G-protein binding site. To assess their molecular level effects, we built structural models of these receptors and performed atomistic molecular dynamics simulations. Most notably, in the Phe290Ser variant we observed the rotameric flip of Trp286(6.48), a putative activation switch that has not been reported in beta(2)AR thus far. In contrast, the variant Met82Lys was found to be the most detrimental to epinephrine binding. Additionally, a few of the nsSNPs were seen to cause perturbations to the lipid bilayer, while a few lead to differences at the G-protein coupling site. We are thus able to classify the variants as ranging from activating to damaging, prioritising them for experimental studies.

Structural-functional insights and studies on saccharide binding of Sophora japonica seed lectin - Yadav, Priya; Shahane, Ganesh; Ramasamy, Sureshkumar; Sengupta, Durba; Gaikwad, Sushama (International Journal of Biological Macromolecules, 2016)
Functional and conformational transitions of the Sophora japonica seed lectin (SJL) were studied in detail using bioinformatics and biophysical tools. Homology model of the lectin displayed all the characteristics of the legume lectin monomer and the experimental observations correlated well with the structural information. In silico studies were performed by protein-ligand docking, calculating the respective binding energies and the residues involved in the interactions were derived from LigPlot(+) analysis. Fluorescence titrations showed three times higher affinity of T-antigen disaccharide than N-acetyl galactosamine (GaINAc) towards SJL indicating extended sugar binding site of the lectin. Thermodynamic parameters of T-antigen binding to SJL indicated the process to be endothermic and entropically driven while those of GaINAc showed biphasic process. SDS-PAGE showed post-translationally modified homotetrameric species of the lectin under native conditions. In presence of guanidine hydrochloride (0.5-5.0 M), the tetramer first dissociated into dimers followed by unfolding of the protein as indicated by size exclusion chromatography, fluorescence and CD spectroscopy. Different structural rearrangements were observed during thermal denaturation of SJL at physiological pH 7.2, native pH 8.5 and molten globule inducing pH 1.0. Topological information revealed by solute quenching studies at respective pH indicated differential hydrophobic environment and charge density around tryptophan residues. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Dissociation; docking; Homology model; Ligand binding; Sophora japonica seed lectin; Thermal transitions

Superior HIV-1 TAR binders with conformationally constrained R52 arginine mimics in the Tat(48-57) peptide - Bhosle, Govind S.; Kharche, Shalmali; Kumar, Santosh; Sengupta, Durba; Maiti, Souvik; Fernandes, Moneesha (Chemmedchem, 2018)
We report a 100-fold increase in binding affinity of the Tat(48-57) peptide to HIV-1 transcriptional activator-responsive element (TAR) RNA by replacing Arg52, an essential and critical residue for Tat's specific binding, with (2S,4S)-4-guanidinoproline. The resulting Tat1M peptide is a far superior binder than Tat1M, a peptide containing another conformationally constrained arginine mimic, (2S,4S)-4-amino-N-(3-guanidinopropyl)proline, or even the control Tat peptide (CtrlTat) itself. Our observations are supported by circular dichroism (CD), isothermal titration calorimetry (ITC), gel electrophoresis and UV spectroscopy studies. Molecular dynamics simulations suggest increased interactions between the more compact Tat1M and TAR RNA, relative to CtrlTat. The CD signature of the RNA itself remains largely unchanged upon binding of the peptides. The Tat mimetics further have better cell uptake properties than the control Tat peptide, thus increasing their potential application as specific TAR-binding molecules.
Keywords: antiviral agents; arginine mimics; RNA; Tat peptide analogues; Tat-TAR binding

Special issue: membrane and receptor dynamics - Prakash, Shikha; Sengupta, Durba (Journal of Membrane Biology, 2019)

Sphingomyelin effects in caveolin-1 mediated membrane curvature published as part of the journal of physical chemistry virtual special issue ``computational and experimental advances in biomembranes'' - Krishna, Anjali; Prakash, Shikha; Sengupta, Durba (Journal of Physical Chemistry B, 2020)
The caveolin-1 (cav-1) protein is an integral component of caveolae and has been reported to colocalize with cholesterol and sphingomyelin-rich curved membrane domains. Here, we analyze the molecular interactions between cav-1 and sphingomyelin containing bilayers using a series of coarse-grain simulations, focusing on lipid clustering and membrane curvature. We considered a palmitoylated-cav-1 construct interacting with phospholipid/cholesterol membranes with asymmetrically distributed sphingomyelin, varying between 5 and 15% in total. We observe that cav-1 binds to the intracellular leaflet and induces a small positive curvature in the leaflet to which it is bound and an opposing negative curvature in the extracellular leaflet. Both cholesterol and sphingomyelin are observed to cluster in cav-1 bound membranes, mainly in the extracellular leaflet. Due to their negative spontaneous curvature, clustering of cholesterol and sphingomyelin facilitates membrane curvature such that the extent of either cholesterol or sphingomyelin clustering is dependent on the curvature induced. Our results suggest that cav-1 binding induces concentration-dependent curvature effects in sphingomyelin-rich membranes. Overall, our work is an important step in understanding the molecular basis of curvature and lipid clustering in cav1 bound cellular membranes.

Substrate induced dynamical remodeling of the binding pocket generates GTPase specificity in DOCK family of guanine nucleotide exchange factors - Roy, Debopriya; Sengupta, Durba; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2022)
Dedicator of cytokinesis (DOCK) family of guanine nucleotide exchange factors (GEFs) activate two members of Rho family GTPases, Rac1/Cdc42, to exert diverse cellular processes, including cell migration. As DOCK GEFs have been critically implicated in tumour cell migration, understanding their function and specificity is imperative for designing anti-metastatic drugs. Based on their GTPase specificity they have been classified as Rac, Cdc42 and dual specific GEFs. Despite extensive structural studies, the factors that determine GTPase specificity of DOCK GEFs have remained elusive. Here, we show that subtle dynamical coupling between GEF and GTPase structures modulate the binding interface to generate mutual spec-ificity. To cluster the dynamically coupled residues in GEF-GTPase complexes a novel intra-residue backbone-torsion-angles based mutual information (TMI) technique was employed. TMI was calcu-lated from 4500 trajectories obtained from a total of 4.5ms molecular dynamics simulations performed on members of all the three clades of DOCK GEFs. The obtained clusters suggest a specificity generation mechanism that involves optimization of the binding pocket for the crucial divergent residue at the 56th position of Rac/Cdc42 (FCdc42/WRac1). These clusters encompass five residues from the structural segment lobe C -a10 helix of the DOCK proteins and functional SWI region of GTPase, which induce orchestrated structural modulations to generate the specificity. Even the conserved residues from SWI region are seen to augment the specificity defining dynamical rearrangements. Furthermore, the pro-posed dynamical GTPase-DOCK GEF specificity model was verified using mutagenesis studies on Rac1 and dual GTPase specific Dock2 and Dock6, respectively. Thus the current study provides the generic substrate specificity determinants of DOCK GEFs, which are not apparent from the conventional struc-tural analysis.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: Dedicator of cytokinesis; GTPase specificity; Guanine exchange factors; Molecular dynamics simulations; Mutual information; Rho GTPases

Synergistic and competitive lipid interactions in the serotonin1A receptor microenvironment - Mohole, Madhura; Sengupta, Durba; Chattopadhyay, Amitabha (ACS Chemical Neuroscience, 2022)
The interaction of lipids with G-protein-coupled receptors (GPCRs) has been shown to modulate and dictate several aspects of GPCR organization and function. Diverse lipid interaction sites have been identified from structural biology, bioinformatics, and molecular dynamics studies. For example, multiple cholesterol interaction sites have been identified in the serotonin1A receptor, along with distinct and overlapping sphingolipid interaction sites. How these lipids interact with each other and what is the resultant effect on the receptor is still not clear. In this work, we have analyzed lipid-lipid crosstalk at the receptor of the serotonin1A receptor embedded in a membrane bilayer that mimics the neuronal membrane composition by long coarse-grain simulations. Using a set of similarity coefficients, we classified lipids that bind at the receptor together as synergistic cobinding, and those that bind individually as competitive. Our results show that certain lipids interact with the serotonin1A receptor in synergy with each other. Not surprisingly, the ganglioside GM1 and cholesterol show a synergistic cobinding, along with the relatively uncommon GM1-phosphatidylethanolamine (PE) and cholesterol-PE synergy. In contrast, certain lipid pairs such as cholesterol and sphingomyelin appear to be in competition at several sites, despite their coexistence in lipid nanodomains. In addition, we observed intralipid competition between two lipid tails, with the receptor exhibiting increased interactions with the unsaturated lipid tails. We believe our work represents an important step in understanding the diversity of GPCR-lipid interactions and exploring synergistic cobinding and competition in natural membranes.
Keywords: GPCR; lipid crosstalk; Martini coarse-grain simulations; Membrane cholesterol; neuronal membranes

Surface-induced demixing of self-assembled isomeric mixtures of citral - Saraf, Deepashri; Prakash, Shikha; Pinjari, Aadil; Pujari, Bhalchandra; Sengupta, Durba (Journal of Molecular Liquids, 2023)
The self-assembly of organic molecules and their interactions with metal surfaces have been of considerable interest, both for developing novel functional materials and for understanding fundamental design principles of nanostructures. In this study, we investigate the solution and surface-induced self-assembly of two stereoisomers of citral molecules (geranial and neral) using atomistic molecular dynamics simulations. We demonstrate that the morphology of the aggregates in water is concentration dependent (ranging from distorted spherical to slab-like aggregates) but independent of isomer effects. The isomeric mixtures of citral indicate homogeneous mixing based on differential density maps and high values of Shannon entropy. Interestingly, surface-confinement of citral aggregates on a Cu(111) surface leads to phase segregation and demixing of the two isomers that is more apparent in the surface-bound monolayer in comparison to the adjacent layers. Positional ordering and formation of domains are observed over a series of isomeric citral mixtures with varying compositions, as indicated by high differential density and low values of Shannon entropy. Our work provides new insights into molecular self-assembly of organic molecules in nanostructures and metal-organic overlayers.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: Citral; Isomers; Metal-organic interactions; molecular dynamics; Self-assembly; Shannon entropy

State-dependent dynamics of extramembrane domains in the β2-adrenergic receptor - Nikte, Siddhanta V.; Joshi, Manali; Sengupta, Durba (Proteins- Structure Function and Bioinformatics, 2024)
G protein-coupled receptors (GPCRs) are membrane-bound signaling proteins that play an essential role in cellular signaling processes. Due to their intrinsic function of transmitting internal signals in response to external cues, these receptors are adapted to be highly dynamic in nature. The beta(2)-adrenergic receptor (beta 2AR) is a representative member of the family that has been extensively analyzed in terms of its structure and activation. Although the structure of the transmembrane domain has been characterized in the different functional states of the receptor, the conformational dynamics of the extramembrane domains, especially the intrinsically disordered regions are still emerging. In this study, we analyze the state-dependent dynamics of extramembrane domains of beta(2)AR using atomistic molecular dynamics simulations. We introduce a parameter, the residue excess dynamics that allows us to better quantify receptor dynamics. Using this measure, we show that the dynamics of the extramembrane domains are sensitive to the receptor state. Interestingly, the ligand-bound intermediate R' state shows the maximal dynamics compared to either the active R*G or inactive R states. Ligand binding appears to be correlated with high residue excess dynamics that are dampened upon G protein coupling. The intracellular loop-3 (ICL3) domain has a tendency to flip towards the membrane upon ligand binding, which could contribute to receptor ``priming.'' We highlight an important ICL1-helix-8 interplay that is broken in the ligand-bound state but is retained in the active state. Overall, our study highlights the importance of characterizing the functional dynamics of the GPCR loop domains.
Keywords: allosteric pathway; beta-2 adrenergic receptor; extramembrane domains; GPCR; loop dynamics; protein dynamics; protein network

Specificity and promiscuity of phosphoinositide lipid interactions with the serotonin1A receptor: insights from submillisecond coarse-grain simulations - Nikte, Siddhanta V.; Sengupta, Durba; Chattopadhyay, Amitabha (ACS Chemical Neuroscience, 2026)
G protein-coupled receptors (GPCRs) are lipid-dependent membrane receptors that serve as important cell signaling hubs. Phosphoinositide (PIP) lipids represent an important class of anionic lipids that play vital roles in neuronal function and signaling. PIP lipids have been reported to modulate GPCR function, although the specificity and molecular details of the interactions are still not clear. An important GPCR in this context is the serotonin(1A) receptor, a neurotransmitter GPCR, which has been reported to interact with phosphatidylinositol 4-phosphate (PIP1) lipids. In this work, we computationally analyzed the specificity of the serotonin(1A) receptor-PIP lipid interactions using coarse-grain molecular dynamics simulations. Our results predict that four anionic lipid sites are present at the receptor surface, although the relative populations are dependent on the lipid type. PIP1 lipids exhibit the highest interaction at a charged cleft formed by transmembrane helices VI and VII. We observed electrostatic interactions at a cluster of charged residues (Arg341, Lys342, Lys345) and hydrophobic and aromatic interactions at residue Ile349 and Tyr402. In contrast, phosphatidylinositol 4,5-bisphosphate (PIP2) and phosphatidylinositol 3,4,5-trisphosphate (PIP3) lipids interact more with transmembrane helix IV. We observed that anionic phospholipids such as phosphatidylserine (PS) interact at these sites, although their occupancy at these sites is much reduced. By elucidating the molecular determinants of these interactions in silico, this study generates novel, testable hypotheses regarding the functional role of specific lipid-receptor contacts. Our work constitutes an important step in analyzing molecular signatures of phosphoinositide lipid-GPCR interactions in the overall context of diverse roles of phosphoinositides in neuronal function and signaling.
Keywords: anionic lipids; Cholesterol; GPCR; MARTINIcoarse-grain simulations; PIP lipids; serotonin(1A) receptor